Fatigue assessment based on hot-spot stresses obtained from the global dynamic analysis and local static sub-model. Issue 1 (1st October 2019) - Viana, Cristiane Oliveira; Carvalho, Hermes; Correia, José; Montenegro, Pedro Aires; Heleno, Raphael Pedrosa; Alencar, Guilherme Santana; Jesus, Abilio M.P. de; Calçada, Rui
Abstract : Purpose: The purpose of this paper is to evaluate the fatigue process through the dynamic analysis of the global structural model and local static sub-modelling in a critical detail using the hot-spot stress approach. The detail was studied in three different positions at the "Alcácer do Sal" access viaduct, and the methodologies from the IIW and Eurocode EN 1993-1-9 were compared. Design/methodology/approach: In this study, the fatigue life process based on the hot-spot stress approach was evaluated using a global dynamic analysis and a local sub-modelling based on a static analysis of welded connections in the "Alcácer do Sal" railway structure, Portugal, taking into consideration the recommendations from IIW and Eurocode EN 1993-1-9. The hot-spot stresses were calculated through the static analysis of the sub-model of the welded connection for each vibration mode with the aim to obtain the temporal stresses using the modal coordinates and modal stresses of the extrapolation points. The Ansys® and Matlab® softwares were used for the numerical analysis and the hot-spot stress calculations, respectively. Findings: The proposed methodology/approach to obtain fatigue assessment is based on the modal analysis of the global structural model and local static sub-modelling. The modal analysis was used to extract the boundary conditions to be used in the local model to determine the temporal stresses of the extrapolation points. Based on the modal superposition method, the stresses as function of time were obtained for fatigue life evaluation of a critical detail by the hot-spot stress approach. The detail was studied in three different positions. Originality/value: In the present study, a global-local fatigue methodology based on dynamic analysis of the global structural model and local static sub-modelling of the critical detail using the hot-spot stress approach is proposed. Herein, the modal analysis of the global structural model supported by the modal superposition method was used to obtain the matrix of modal coordinates. The static analysis of the local sub-model for each mode from the modal analysis of global structural model was done to estimate the hot-spot stresses. The fatigue damage calculation was based on S-N curve of the critical detail and rainflow method. The IIW recommendation proved to be more conservative compared to the proposed rules in the Eurocode EN 1993-1-9. The global-local modelling based on dynamic analysis is an important and effective tool for fatigue evaluation in welded joints.